A Comprehensive Analysis of B2B Content Creation Challenges, Best Practices, and the Impact of AI & Technology - Pandey, Saurabh (Digital Repository of Theses - SSBM Geneva, 2025)
In an age characterized by digital transformation and informed enterprise purchasing in the B2B sector, content has emerged as a crucial factor in shaping the decisions of key stakeholders throughout the purchase process. This dissertation examines the complex issues encountered by B2B marketers in developing effective content, identifies current best practices, and analyzes the increasing influence of artificial intelligence (AI) and technology in revolutionizing content tactics on a large scale. The study employed a structured, quantitative research design to survey 100 seasoned B2B marketers from mid-to-large firms in India using LinkedIn. The poll examined the frequency of content generation, formats, budget distribution, utilization of AI tools, and alignment with buyer personas and decision -making phases. Data was examined using descriptive and inferential statistics to produce actionable insights. Research indicates that content development in B2B environments is resource-demanding, with podcasts, webinars, and whitepapers serving as impactful yet time-consuming formats. Although most of the content is produced for the awareness stage, marketers recognize the necessity to more effectively connect content with the consideration, decision, and loyalty stages. Buyer personas and journey phases significantly impact content strategy and budgeting; nonetheless, deficiencies persist in attaining personalization and accurately quantifying ROI. The report additionally identified a growing dependence on AI tools for content discovery, production, and performance evaluation. Nonetheless, although AI has enhanced efficiency and scalability, apprehensions over content quality and inventiveness remain. The study highlights the significance of cohesive, persona-focused content strategy bolstered by technology while warning against excessive dependence on automation. It necessitates a more sophisticated comprehension of content preferences among decision-makers, strategic content reutilization, and outcome-oriented measurement frameworks. This dissertation enhances the current literature by providing an empirical, India-centric analysis of B2B content marketing and emphasizing the interaction between human insight and AI in the creation of effective content. It offers pragmatic suggestions for firms aiming to enhance content operations and elevate engagement with varied B2B stakeholders in a progressively digital and data-centric marketplace.